Utility of 3D double-echo steady-state with water excitation (3D-DESS-WE) in diagnosing intraparotid facial nerve schwannoma: A case report - Akito Sano; Akira Baba; Koshi Ikeda; Hisashi Kessoku; Reina Kayama; Satoshi Matsushima; Hideomi Yamauchi; Shota Tasaki; Rihito Nakazato; Hiroya Ojiri (Radiology Case Reports, 2025)
Differentiating intraparotid facial nerve schwannoma from other parotid tumors, particularly pleomorphic adenoma, is clinically crucial due to significant differences in treatment approaches. We report a case of a male patient in his 70s presenting with a left parotid mass. Magnetic Resonance Imaging (MRI) revealed a mass within the left parotid gland exhibiting the characteristic ``target sign''. The 3D double-echo steady-state with water excitation (3D-DESS-WE) MRI sequence demonstrated continuity between the mass and the facial nerve, a finding that significantly contributed to the diagnosis. Histopathological examination confirmed the diagnosis of schwannoma. This case highlights the potential of the 3D-DESS-WE sequence, in addition to conventional MRI signs, in improving the diagnostic accuracy of intraparotid facial nerve schwannomas.